PENDEKATAN TEORI PERMAINAN DALAM MENENTUKAN MODEL HARGA EQUILIBRIUM PADA RANTAI PASOK SORGUM DI DESA KAWALELO - YEREMIAS SABON MUKIN; JUSRRY ROSALINA PAHNAEL; MIRA WADU; ROBERUS DOLE GUNTUR (E-Jurnal Matematika, 2026)
This study aims to analyze the determination of equilibrium prices in the sorghum supply chain involving suppliers, distributors, and retailers using a game theory approach. The research was conducted in Kawalelo Village, Demon Pagong District, East Flores Regency, Indonesia, using primary data collected through interviews and questionnaires administered to 53 respondents, consisting of 42 suppliers, 2 distributors, and 9 retailers. The analysis was carried out by constructing payoff matrices, determining best responses, and identifying Nash Equilibrium strategies. The results indicate that game theory is capable of modeling the strategic interactions among supply chain actors in determining optimal pricing decisions. The equilibrium strategy for the supplier–retailer combination is (High, High), while the equilibrium strategy for the distributor–retailer combination is (Low, High). Factors influencing the formation of equilibrium prices include production and distribution cost structures, purchase and selling price levels, production volume, and interactions among supply chain participants. The resulting equilibrium pricing model demonstrates the potential to improve supply chain efficiency and achieve a more proportional distribution of profits, thereby supporting farmers' welfare and the development of sorghum as an agricultural commodity in East Flores.